2004
DOI: 10.1182/blood-2004-04-1428
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of lymphatic vessels through NF-κB activity

Abstract: The molecular biology of lymphatics is only rudimentary owing to the long-standing absence of specific markers, and scanty is the information regarding bladder lymphatic vessels. By using mice with a reporter gene for nuclear factor B (NF-B) activity (B-lacZ) in combination with immunohistochemical staining with a specific lymphatic marker (LYVE-1), we show, for the first time, that NF-B is constitutively active in lymphatic endothelium in the urinary bladder, uterus, intestine, heart, and airways. Tie2-lacZ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 9 publications
4
43
0
Order By: Relevance
“…26 Upon NF-B activation in these mice, one of the NF-B subunits, p65, translocates to the nucleus and binds the p105 promoter, which induces lacZ expression. Consistent with a previous report, 33 NF-B was predominantly expressed in LYVE-1 ϩ lymphatic capillaries, but not in the blood vessel of the diaphragm (Figure S4 top panel). Moreover, the LPS-induced, newly developed branching lymphatic vessels also expressed NF-B (Figure S4 bottom panel).…”
Section: Tlr4 In Lecs Is a Functional Receptor Mediating Lps-induced supporting
confidence: 92%
“…26 Upon NF-B activation in these mice, one of the NF-B subunits, p65, translocates to the nucleus and binds the p105 promoter, which induces lacZ expression. Consistent with a previous report, 33 NF-B was predominantly expressed in LYVE-1 ϩ lymphatic capillaries, but not in the blood vessel of the diaphragm (Figure S4 top panel). Moreover, the LPS-induced, newly developed branching lymphatic vessels also expressed NF-B (Figure S4 bottom panel).…”
Section: Tlr4 In Lecs Is a Functional Receptor Mediating Lps-induced supporting
confidence: 92%
“…Alternatively, nuclear factor-B activity has been fortuitously associated with lymphatic vessels. 25 This LacZ reporter-based model, however, has drawbacks of ubiquitous nuclear factor-B expression in other cell types under various physiologic and pathologic conditions. Despite the creation of the Prox1-GFP transgenic mouse as part of the GENSAT effort many years ago, its experimental value in vascular research has never been explored to date.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of Tie2 with its ligand angiopoietin-1 (Ang1) helps remodel and stabilize primitive vasculature (Sato et al 1993;Suri et al 1996). The phenotype of mice lacking another Tie2 ligand, Ang2, suggested that Tie2 also functions during postnatal lymphatic remodeling (Gale et al 2002); however, its expression has not been observed in LECs (Motoike et al 2000;Saban et al 2004;Wilting et al 2006), except in restricted regions of adult lymphatics Tammela et al 2005). Hence, Tie2-independent, integrin-mediated signaling might mediate angiopoietin function in the lymphatic vasculature .…”
Section: Lymphatic Vasculature Is Of Venous Originmentioning
confidence: 99%